OP0027 TIME TO FLARE AND GLUCOCORTICOID EXPOSURE IN PATIENTS WITH NEW-ONSET VERSUS RELAPSING GIANT CELL ARTERITIS TREATED WITH TOCILIZUMAB OR PLACEBO PLUS PREDNISONE TAPERING: 3-YEAR RESULTS FROM A RANDOMIZED CONTROLLED PHASE 3 TRIAL. (2nd June 2020) - Stone, J. H.; Spotswood, H.; Unizony, S.; Aringer, M.; Blockmans, D.; Brouwer, E.; Cid, M. C.; Dasgupta, B.; Rech, J.; Salvarani, C.; Spiera, R.; Bao, M.
Abstract : Background: In part 1 of the 52-week, double-blind GiACTA trial, tocilizumab (TCZ) every week (QW) or every other week (Q2W) + prednisone tapering reduced the risk for flare versus placebo (PBO) + 26-week prednisone tapering among patients with new-onset giant cell arteritis (GCA) at baseline. Among patients with relapsing GCA, TCZ QW but not Q2W + prednisone reduced the risk for flare versus both PBO groups, and there was separation in the time to flare between the TCZ QW and Q2W groups. 1 Objectives: To report time to first flare and potential cumulative glucocorticoid (GC) sparing over 3 years of the GiACTA trial (part 1 + 2-year open-label part 2) among patients with new-onset or relapsing GCA. Methods: At the end of part 1, patients entered open-label part 2, in which GCA therapy (including initiation/termination of open-label TCZ and/or GCs) was given at the investigator's discretion according to disease status. Time to first GCA flare during the 3-year study period was assessed using Kaplan-Meier analysis for patients in the intention-to-treat population according to disease onset status at baseline (new-onset/relapsing) based on their originally assigned treatment groups: TCZ QW, TCZ Q2W, or pooled PBO (PBO+26-week and PBO+52-week prednisone taper). Results: Among patients randomly assigned in part 1, 47 of 100 (47%) in the TCZ QW group, 26 of 49 (53%) in the TCZ Q2W group, and 46 of 101 (46%) in the pooled PBO group had new-onset GCA at baseline; the rest had relapsing GCA. Median time to first flare over 3 years was longer for patients assigned to TCZ treatment in part 1 than for patients assigned to PBO; Kaplan-Meier analysis showed a clear separation between the TCZ QW and the pooled PBO groups over 3 years for patients with new-onset and relapsing GCA (Figure 1A ). Separation between the TCZ QW and TCZ Q2W groups was also observed over 3 years in patients with new-onset and relapsing GCA, although this was more evident in patients with relapsing GCA (Figure 1B ). Higher proportions of patients in the TCZ QW group (new-onset, 49%; relapsing, 47%) than the pooled PBO group (new-onset, 28%; relapsing, 31%) and the TCZ Q2W group (new-onset, 27%; relapsing, 35%) remained flare-free during their entire treatment period. Cumulative prednisone dose over 3 years was lower for patients originally assigned to TCZ QW versus those originally assigned to PBO for patients with new-onset GCA and those with relapsing GCA at baseline (Figure 2 ). Conclusion: In this 3-year analysis of GiACTA parts 1 and 2, time to first flare favored TCZ QW over TCZ Q2W in patients with new-onset and relapsing GCA. TCZ QW delayed time to first flare and resulted in lower cumulative GC exposure compared with PBO in patients with new-onset and relapsing GCA, supporting TCZ QW dosing in patients with GCA regardless of disease onset. References: [1]Stone JH et al. N Engl J Med 2017;377:317-28. Disclosure of Interests: John H. Stone Grant/research support from: Roche, Consultant of: Roche, Helen Spotswood Shareholder of: Roche Products Ltd, Employee of: Roche Products Ltd, Sebastian Unizony Grant/research support from: Genentech, Inc., Martin Aringer Consultant of: Boehringer Ingelheim, Roche, Speakers bureau: Boehringer Ingelheim, Roche, Daniel Blockmans Consultant of: yes, Speakers bureau: yes, Elisabeth Brouwer Consultant of: Roche (consultancy fee 2017 and 2018 paid to the UMCG), Speakers bureau: Roche (2017 and 2018 paid to the UMCG), Maria C. Cid Speakers bureau: Roche, Bhaskar Dasgupta Grant/research support from: Roche, Consultant of: Roche, Sanofi, GSK, BMS, AbbVie, Speakers bureau: Roche, Jürgen Rech Consultant of: BMS, Celgene, Novartis, Roche, Chugai, Speakers bureau: AbbVie, Biogen, BMS, Celgene, MSD, Novartis, Roche, Chugai, Pfizer, Lilly, Carlo Salvarani: None declared, Robert Spiera Grant/research support from: Roche-Genetech, GSK, Boehringer Ingelheim, Chemocentryx, Corbus, Forbius, Sanofi, Inflarx, Consultant of: Roche-Genetech, GSK, CSL Behring, Sanofi, Janssen, Chemocentryx, Forbius, Mistubishi Tanabe, Min Bao Shareholder of: Roche, Employee of: Genentech